Hospital admission for hyperemesis gravidarum: a nationwide study of occurrence, reoccurrence and risk factors among 8.2 million pregnancies - Fiaschi, Linda; Nelson-Piercy, Catherine; Tata, Laila J. (Oxford University Press, 2016)
STUDY QUESTION: What are the maternal risk factors for hyperemesis gravidarum (HG) hospital admission, readmission and reoccurrence in a following pregnancy? SUMMARY ANSWER: Young age, less socioeconomic deprivation, nulliparity, Asian or Black ethnicity, female fetus, multiple pregnancy, history of HG in a previous pregnancy, thyroid and parathyroid dysfunction, hypercholesterolemia and Type 1 diabetes are all risk factors for HG. WHAT IS KNOWN ALREADY: Women with Black or Asian ethnicity, of young age, carrying multiple babies or singleton females, with Type 1 diabetes or with a history of HG were previously reported to be at higher risk of developing HG; however, most evidence is from small studies. Little is known about associations with other comorbidities and there is controversy over other risk factors such as parity. Estimates of HG prevalence vary and there is a little understanding of the risks of HG readmission in a current pregnancy and reoccurrence rates in subsequent pregnancies, all of which are needed for planning measures to reduce onset or worsening of the condition. STUDY DESIGN, SIZE, DURATION: We performed a population-based cohort study of pregnancies ending in live births and stillbirths using prospectively recorded secondary care records (Hospital Episode Statistics) from England. We analysed those computerized and anonymized clinical records from over 5.3 million women who had one or more pregnancies between 1997 and 2012. PARTICIPANTS/MATERIALS, SETTING, METHODS: We obtained 8 215 538 pregnancies from 5 329 101 women of reproductive age, with a total of 186 800 HG admissions occurring during 121 885 pregnancies. Multivariate logistic regression with generalized estimating equations was employed to estimate odds ratios (aOR) to assess sociodemographic, pregnancy and comorbidity risk factors for HG onset, HG readmission within a pregnancy and reoccurrence in a subsequent pregnancy. MAIN RESULTS AND THE ROLE OF CHANCE: Being younger, from a less socioeconomically deprived status, of Asian or Black ethnicity, carrying a female fetus or having a multiple pregnancy all significantly increased HG and readmission risk but only ethnicity increased reoccurrence. Comorbidities most strongly associated with HG were parathyroid dysfunction (aOR = 3.83, 95% confidence interval 2.28–6.44), hypercholesterolemia (aOR = 2.54, 1.88–3.44), Type 1 diabetes (aOR = 1.95, 1.82–2.09), and thyroid dysfunction (aOR = 1.85, 1.74–1.96). History of HG was the strongest independent risk factor (aOR = 4.74, 4.46–5.05). Women with higher parity had a lower risk of HG compared with nulliparous women (aOR = 0.90, 0.89–0.91), which was not explained by women with HG curtailing further pregnancies. LIMITATIONS, REASONS FOR CAUTION: Although this represents the largest population-based study worldwide on the topic, the results could have been biased by residual and unmeasured confounding considering that some potential important risk factors such as smoking, BMI or prenatal care could not be measured with these data. Underestimation of non-routinely screened comorbidities such as hypercholesterolemia or thyroid dysfunction could also be a cause of selection bias. WIDER IMPLICATIONS OF THE FINDINGS: The estimated prevalence of 1.5% from our study was similar to the average prevalence reported in the literature and the representativeness of our data has been validated by comparison to national statistics. Also the prevalence of comorbidities was mostly similar to other studies estimating these in the UK and other developed countries. Women with Black or Asian ethnicity, of young age, carrying multiple babies or singleton females, with Type 1 diabetes or with history of HG were confirmed to be at higher risk of HG with an unprecedented higher statistical power. We showed for the first time that socioeconomic status interacts with maternal age, that hypercholesterolemia is a potential risk factor for HG and that carrying multiple females increases risk of hyperemesis compared with multiple males. We also provided robust evidence for the association of parity with HG. Earlier recognition and management of symptoms via gynaecology day-case units or general practitioner services can inform prevention and control of consequent hospital admissions. STUDY FUNDING/COMPETING INTEREST(S): The work was founded by The Rosetrees Trust and the Stoneygate Trust. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. C.N.-P. reports personal fees from Sanofi Aventis, Warner Chilcott, Leo Pharma, UCB and Falk, outside the submitted work and she is one of the co-developers of the RCOG Green Top Guideline on HG; all other authors did not report any potential conflicts of interest.